Preliminary Data on Silybum marianum Metabolites: Comprehensive Characterization, Antioxidant, Antidiabetic, Antimicrobial Activities, LC-MS/MS Profiling, and Predicted ADMET Analysis - Sabrina Lekmine; Ouided Benslama; Mohammad Shamsul Ola; Nabil Touzout; Hamza Moussa; Hichem Tahraoui; Haroun Hafsa; Jie Zhang; Abdeltif Amrane (Metabolites)
Background/Objectives: Silybum marianum extract, obtained via microwave-enhanced extraction, was evaluated for its antioxidant, antidiabetic, and antimicrobial activities to explore its therapeutic potential. Methods: The extraction was performed using microwave-enhanced techniques, and LC-MS/MS was employed to profile the metabolites in the extract. Total phenolic and flavonoid contents were quantified using spectrophotometric methods. Antioxidant activity was assessed using DPPH, ABTS, CUPRAC, Phenanthroline, and FRAP assays. Enzyme inhibition assays were conducted to evaluate antidiabetic activity against α-glucosidase and α-amylase. Antimicrobial activity was determined using the disc diffusion method, and in silico ADMET and drug-likeness analyses were performed for key metabolites. Results: The extract contained 251.2 ± 1.2 mg GAE/g of total phenolics and 125.1 ± 1.6 mg QE/g of total flavonoids, with 33 metabolites identified, including phenolic acids, tannins, flavonoids, and flavolignans. Strong antioxidant activity was observed, with IC50 values of 19.2 ± 2.3 μg/mL (DPPH), 7.2 ± 1.7 μg/mL (ABTS), 22.2 ± 1.2 μg/mL (CUPRAC), 35.2 ± 1.8 μg/mL (Phenanthroline), and 24.1 ± 1.2 μg/mL (FRAP). Antidiabetic effects were significant, with IC50 values of 18.1 ± 1.7 μg/mL (α-glucosidase) and 26.5 ± 1.3 μg/mL (α-amylase). Antimicrobial activity demonstrated inhibition zones of 8.9 ± 1.1 mm (Bacillus subtilis), 12.6 ± 1.6 mm (Escherichia coli), 8.2 ± 1.2 mm (Fusarium oxysporum), and 9.2 ± 1.1 mm (Aspergillus niger). In silico analyses showed high absorption, favorable metabolism and excretion, and minimal toxicity, with no hERG channel inhibition or hepatotoxicity. Conclusions: The comprehensive results highlight the significant antioxidant, antidiabetic, and antimicrobial activities of S. marianum extract, suggesting its potential for therapeutic and preventive applications.